The Teodorín Situation (Part I): Presidential Succession in Equatorial Guinea (Comillas Journal of International Relations, 2023)
The essay is divided and published into two parts: each separately assessing the main recent trends in the national and international politics of Equatorial Guinea — roughly between the Covid-19 crisis and May 2023. Part I profiles the current vice president, Teodoro Nguema Obiang Mangue, widely known by his moniker Teodorín. His dynastic succession seems practically set in stone and quite imminent, given that his father, the president, Teodoro Obiang Nguema Mbasogo, is an octogenarian and has recently shown many signs of an already effectively retired. Part I focuses on Teodorín’s populist policy style, the demotion and persecution of contenders, and the punishment of anti-government figures both within and outside the country, which have served to display and consolidate his domestic ascension to power. The combined introduction in part I, and the conclusion in part II outlines the recent shifts across the domestic political, international geopolitical, and economic domains, that have marked and steered Teodorín’s active and seemingly inevitable rise to the presidency of Equatorial Guinea.
Keywords: Equatorial Guinea; Teodoro Nguema Obiang Mangue; electoral autocracies; presidential succession